2013
DOI: 10.1371/journal.pone.0077523
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Treatment Inhibits Hypoxia-Inducible Factor 1α Accumulation and Protects against Burn-Induced Gut Barrier Dysfunction in a Rodent Model

Abstract: ObjectiveBurn-induced gut dysfunction plays an important role in the development of sepsis and multiple organ dysfunction. Emerging evidence suggests that hypoxia-inducible factor-1α (HIF-1α) is critical in paracelluar barrier functions via regulating vascular endothelial growth factor (VEGF) and myosin light chain kinase (MLCK) expression. Previous studies have also demonstrated that histone deacetylase inhibitors (HDACIs) can repress HIF-1α. This study aims to examine whether valproic acid (VPA), a HDACI, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 50 publications
2
29
0
1
Order By: Relevance
“…It has been suggested that sepsis is caused by an exaggerated inflammatory response, which may develop into septic shock and multiple organ dysfunction syndrome (3). During a severe infection, intestinal barrier dysfunction may lead to ischemia and hypoxia, both of which have an important role in the development of sepsis (4). In addition, emerging evidence suggests that the intestinal tract is not only a target of the inflammatory response, but may also be the starting point for multiple organ dysfunction (5).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that sepsis is caused by an exaggerated inflammatory response, which may develop into septic shock and multiple organ dysfunction syndrome (3). During a severe infection, intestinal barrier dysfunction may lead to ischemia and hypoxia, both of which have an important role in the development of sepsis (4). In addition, emerging evidence suggests that the intestinal tract is not only a target of the inflammatory response, but may also be the starting point for multiple organ dysfunction (5).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated that ERK phosphorylation contributes to the activation of the MLCK signaling pathway, which leads to barrier dysfunction in the vascular endothelium or intestinal epithelium [6]. Although MLCK is implicated in endothelial and epithelial barrier dysfunction [25,26], its specific role in the impairment of the esophageal epithelial barrier has not been reported. Our study provides direct evidence that ERK-mediated activation of MLCK plays a critical role in esophageal epithelial barrier dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the HDAC inhibitor valproic acid (VPA), was beneficial in lethal burn models in rats and dogs. In rats, VPA treatment improved survival and gut barrier dysfunction and attenuated brain and cardiac injury [190,191]. In dogs, VPA improved survival, hemodynamics, and intestinal perfusion, and reduced circulating levels of the pro-inflammatory cytokine, TNF-α.…”
Section: Clinical Managementmentioning
confidence: 99%